Sex Sirens in the Novel, Making the Minister Smile: Exploring the Consequences of Western Cultural Influence on Love and Sex in Indian Society (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Making the Minister Smile depicts a topsy-turvy picture regarding love and sex. Here Indian ladies influenced by the western culture are shown as very free and daring in fulfilling their romantic and carnal desires. They simply want to keep the affairs secret. They are shown as loving wives who feign chastity to their husbands to keep them happy and contended. But they would prefer the whole affairs in their own terms and conditions and would easily get hurt if their pride is offended. The traditional roles are subverted mainly because of western education or cultural influence.